Calcineurin is essential in cyclosporin A- and FK506-sensitive yeast strains. - Breuder, T (1994)
The immunophilin-immunosuppressant complexes cyclophilin-cyclosporin A (CsA) and FKBP12-FK506 inhibit the phosphatase calcineurin to block T-cell activation. Although cyclophilin A, FKBP12, and calcineurin are highly conserved from yeast to man, none had previously been shown to be essential for viability. We find that CsA-sensitive yeast strains are FK506 hypersensitive and demonstrate that calcineurin is required for viability in these strains. Mutants lacking cyclophilin A or FKBP12 are resistant to CsA or FK506, respectively. Thus, both the immunosuppressive and the antifungal actions of CsA and FK506 result from calcineurin inhibition by immunophilin-drug complexes. In yeast strains in which calcineurin is not essential, calcineurin inhibition or mutation of calcineurin confers hypersensitivity to LiCl or NaCl, suggesting that calcineurin regulates cation transport.